Hemoglobin glutamer‐250 (bovine) in South Africa: consensus usage guidelines from clinician experts who have treated patients. Issue 10 (23rd September 2016) - Mer, Mervyn; Hodgson, Eric; Wallis, Lee; Jacobson, Barry; Levien, Lewis; Snyman, Jacques; Sussman, Martin J.; James, Mike; van Gelder, Antoine; Allgaier, Rachel; Jahr, Jonathan S.
Abstract : Hemopure (hemoglobin glutamer‐250 [bovine]; HBOC‐201) is a hemoglobin (Hb)‐based oxygen carrier registered with the Medicines Control Council of South Africa. It is indicated for the treatment of adult patients who are acutely anemic, for the purpose of maintaining tissue oxygen delivery thus eliminating, delaying, or reducing the need for allogeneic red blood cells (RBCs). Hemopure is a volume expander, and circulatory volume must be carefully monitored for signs of fluid overload. Hemopure is not as effective as RBCs for restoring Hb content and concentration, but in cases of severe anemia where allogeneic blood is not an option or is unavailable, it may offer an immediate alternative for improving oxygen transport. This document provides clinical recommendations on the safe and effective use of Hemopure based on the postmarketing experience in South Africa as well as a better understanding of Hemopure properties reflected in recent publications.